2022
DOI: 10.3390/ijms231810899
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Graphene Content on the Antibacterial Properties of Polycaprolactone

Abstract: This work contains an analysis of the impact of modifying a bioresorbable polymer—polycaprolactone (PCL)—with various additives on its antibacterial properties. To this end, samples of PCL filament containing various content levels of graphene (GNP), 0.5%, 5%, 10%, were obtained using injection molding. Polymer samples without additives were used for comparison. The next step was to assess the antimicrobial impact of the preparations under study against the following microorganisms: Staphylococcus aureus ATCC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 28 publications
0
8
1
Order By: Relevance
“…However the profound antibacterial activity of FCZ‐ZnO‐HAp‐PCL nanocomposite may be due to presence of PCL and HAp NPs. PCL shows activity against microbes likes E. coli when it is modified with other metals or metal oxides and hydroxyapatite exhibited exhibit profound antibacterial properties against both Gram‐positive and Gram‐negative bacteria [39,40] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However the profound antibacterial activity of FCZ‐ZnO‐HAp‐PCL nanocomposite may be due to presence of PCL and HAp NPs. PCL shows activity against microbes likes E. coli when it is modified with other metals or metal oxides and hydroxyapatite exhibited exhibit profound antibacterial properties against both Gram‐positive and Gram‐negative bacteria [39,40] …”
Section: Resultsmentioning
confidence: 99%
“…PCL shows activity against microbes likes E. coli when it is modified with other metals or metal oxides and hydroxyapatite exhibited exhibit profound antibacterial properties against both Grampositive and Gram-negative bacteria. [39,40] The antifungal activity analysis of ZnO, HAp, and the FCZ-ZnO-HAp-PCL composite against Candida albicans and Aspergillus niger at varying concentrations of 10 μg mL À 1 , 30 μg mL À 1 , 100 μg mL À 1 by the well diffusion method is shown in Table 2. The results showed that FCZ-ZnO-HAp-PCL nanocomposite was more effective in inhibiting exercise than ZnO and HAp nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…Among several polymers, polycaprolactone (PCL) is a promising biomaterial for bone regeneration in the medical field due to its numerous properties. In particular, PCL is a highly biocompatible and bioresorbable polymer that, upon its implantation, is not necessary to remove at the end of its function [ 4 , 5 ]. PCL is also a suitable biomaterial for producing three-dimensional (3D) constructs, called scaffolds, which are an advanced therapeutic solution for cavity-filling in bone disease or for the healing of fractured bone [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we were successful in developing pure PCL filament sticks using injection molding and successfully used them for FDM [ 28 ]. As a further improvement, we produced composite filaments made of a PCL matrix with 0.5, 5, 10 percentages of graphene as a filler [ 29 , 30 ]. We have already proved that the addition of small amounts of graphene, bioglass or zinc-doped bioglass significantly enhance PCL antibacterial efficacy [ 31 ] and that the presence of Zn 2+ ions in the electrospun polycaprolactone membranes influence the osteogenic differentiation of cells [ 32 ].…”
Section: Introductionmentioning
confidence: 99%